Investigating the inhibitory activity and mechanism differences between norartocarpetin and luteolin for tyrosinase: A combinatory kinetic study and computational simulation analysis. (15th May 2017) - Zhang, Long; Zhao, Xin; Tao, Guan-Jun; Chen, Jie; Zheng, Zong-Ping
Highlights: Norartocarpetin and luteolin display different tyrosinase kinetic manners. Both norartocarpetin and luteolin show a static type quenching mechanism. Norartocarpetin is an inhibitor yet luteolin is a substrate or a suicide one. Norartocarpetin interacts with Asn81 and His85 in tyrosinase active pocket. Luteolin hydroxyl groups at B ring bounded tyrosinase residues Asn81 and Cys83. Abstract: Flavonoids are an important type of natural tyrosinase inhibitor, but their inhibitory activity and mechanism against tyrosinase are very different because of their different structures. In this study, the inhibitory activity and mechanism differences between norartocarpetin and luteolin for tyrosinase were investigated by a combination of kinetic studies and computational simulations. The kinetic analysis showed that norartocarpetin reversibly inhibited tyrosinase in a competitive manner, whereas luteolin caused reversible noncompetitive inhibition. Both norartocarpetin and luteolin showed a single type of quenching and a static-type quenching mechanism. A computational simulation indicated that the hydroxyl groups of the B ring of norartocarpetin interacted with tyrosinase residues Asn81 and His85 in the active pocket, while the hydroxyl groups of the B ring of luteolin bound residues Asn81 and Cys83. HPLC and UPLC-MS/MS further confirmed that luteolin acted as a substrate or a suicide inhibitor, yet norartocarpetin acted as an inhibitor.